The Importance of the Library in Medical Education - Ravdin, I. S. (1965)
The medical library assumes increasing importance to teaching and research. While funds for research, medical education, and improved facilities for patients have been increasing and are relatively easy to obtain, however, it has been extraordinarily difficult to obtain funds for the building and maintenance of medical libraries. The National Library of Medicine is attempting to preserve the record of medical knowledge and by means of mechanization provide more efficient service to physicians and scientists, but one, or a few, great libraries cannot serve the medical interests of the country. Federal support such as the program of grants in the proposed Medical Library Assistance Act is needed to assist local and regional efforts to improve library service.